2004
DOI: 10.1016/j.femsle.2004.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effects of sanitizers against planktonic and sessile Listeria monocytogenes cells according to the growth phase

Abstract: This study was designed to investigate the individual or combined effects of sanitizers on survival of planktonic or sessile Listeria monocytogenes cells at different phase of growth. The sanitizers tested included: (i) acetic acid (pH 5.0), (ii) NaOH (pH 12.0), (iii) 10% Na2SO4, (iv) 10% Na2SO4 and acetic acid (pH 5.0), (v) 10% Na2SO4 and NaOH (pH 12.0), (vi) a quaternary ammonium (20 ppm) and (vii) glyceryl monolaurate (75 ppm). Results revealed a great efficacy of alkaline treatments on both sessile and pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 39 publications
0
27
1
1
Order By: Relevance
“…Previous studies have demonstrated that bacteria in biofilms, whether present as a single species or multi-species biofilm, show a greater level of resistance to several physicochemical stresses such as antibacterial agents (Berrang, Frank, & Meinersmann, 2008;Folsom et al, 2006;Pan, Breidt, & Kathariou, 2006;van der Veen & Abee, 2011;Yang et al, 2009). Studies have also shown that biofilm resistance is related to the age of the biofilm (Belessi, Gounadaki, Psomas, & Skandamis, 2011;Chavant, Gaillard-Martinie, & Hebraud, 2004;Ibusquiza, Herrera, & Cabo, 2011). In the present work this resistance was clearly observed in a 48-h biofilm.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that bacteria in biofilms, whether present as a single species or multi-species biofilm, show a greater level of resistance to several physicochemical stresses such as antibacterial agents (Berrang, Frank, & Meinersmann, 2008;Folsom et al, 2006;Pan, Breidt, & Kathariou, 2006;van der Veen & Abee, 2011;Yang et al, 2009). Studies have also shown that biofilm resistance is related to the age of the biofilm (Belessi, Gounadaki, Psomas, & Skandamis, 2011;Chavant, Gaillard-Martinie, & Hebraud, 2004;Ibusquiza, Herrera, & Cabo, 2011). In the present work this resistance was clearly observed in a 48-h biofilm.…”
Section: Resultsmentioning
confidence: 99%
“…In Europe 14 cases of human listeriosis were reported in 2009 in a "Quargel" cheese-associated outbreak that affected Austria and Germany resulting in 3 deaths and the recall of these products (Fretz et al, 2010). Several reasons have been postulated to explain the apparent deficient control of this pathogen in food industry: lack of sensitivity among methods leading to an inadequate L. monocytogenes detection due to the existence of viable non cultivable cells (Dinu et al, 2009;Dreux et al, 2007), inefficient procedures for cleaning and disinfection (Campdepadrós et al, 2012) and principally biofilm formation by L. monocytogenes and subsequent increase of its capability to resist sanitizers (Chavant et al, 2004;Ibusquiza et al, 2011;Pan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Surface associated microbial biofilms resist desiccation, UV light, and treatment with antimicrobial and sanitizing agents, due to diffusion of antimicrobials, metabolic activity of biofilm cells, and/or phenotypic variability within the biofilm (Parsek & Fuqua, 2004). Several antimicrobial agents and sanitizers have been used in an attempt to prevent biofilm formation in the food industry (Chavant, Gaillard-Martinie, & Hébraud, 2004;Robbins, Fisher, Moltz, & Martin, 2005).…”
Section: Introductionmentioning
confidence: 99%